A Phenomenological Approach to the Cultivation of Expertise: Emergent Understandings of Autism. (June 2017) - Lawlor, Mary C.; Solomon, Olga
Abstract: In this article, we draw on narrative phenomenological (Mattingly 2010) and ethnographic projects to investigate how phenomenology may contribute to understanding how practical, experientially gained, expertise is cultivated in extraordinary circumstances. The lived world of autism provides a compelling context for such an exploration. Drawing on ethnographic data, we present arguments related to how a phenomenological approach to understanding autism can be productive by examining the cultivation of expertise and the contagion of knowledge and understanding. Family expertise that is grounded in lived experience often reveals the limitations of both public knowledge and scientific evidence and is generative of a kind of practical knowledge that warrants diffusion. Consideration is given to the specific contributions of a phenomenological approach to understanding autism and learning in collective engagements. Contagion as both a facilitative and positive phenomenon and a potentially stressful or harmful development is discussed.